Performance analysis of interpolators for elaboration of pH map for family farms - Marteli, Alice Nardoni [UNESP]; Piroli, Edson Luis [UNESP] (Univ Estadual Centro-oeste, 2015)
The aim of this research was to analyze interpolators applied at differentspacings of soil sample collections for the elaborationof pH maps on small farms which fell into the category of Family Farming in Ourinhos region, SP, Brazil. The techniques used followed the foundations of precision agriculture, with adjustments geared to small farmers so that the analysis of the basic data of the soil dispense the use of expensive equipment that is inaccessible to this public. Forthe development of this research were made collections of georeferenced soil samples in field, analyses of the soil samples were made at the soils laboratory at the Unesp - Ourinhos Campus and the spatial distribution of the results in maps that was generated starting from interpolation techniques and Geoprocessing. The interpolatorrated as the most suitable for the proposed objectives was the TIN (Triangular Irregular Network), because its accuracy didn't depend on the number of samples. Moreover, it can be applied by people with basic computer skills and geoprocessing.
Keywords: TIN; TREND; Kriging; family farms; precision agriculture